Typification of Mexican Euphorbia (Euphorbiaceae) - Steinmann, Victor W. (Phytotaxa, 2023)
Euphorbia is one of the largest genera of flowering plants, and Mexico is one of the primary centers of diversification. Much work remains before a thorough understanding of the Mexican species is reached, and the present contribution aims to unambiguously allow the application of 14 names by clarifying their types. Some of these are distributed outside of Mexico, including Canada, the United States, Central America, South America, and the Antilles. Lectotypes of the following names are designated: E. biformis, E. boliviana, E. elastica, E. gumaroi, E. lancifolia, E. luciismithii, E. macropus, E. mendezii, E. potosina, E. subreniformis, and E. umbellulata. In the absence of original material, neotypes are selected for the following names: E. nudiflora, E. tanquahuete, and E. vermiculata. All the names are currently accepted, except for E. elastica (=E. tanquahuete) and E. biformis (=E. macropus).